STUDI KOMPARATIF PARTISIPASI POLITIK PENYANDANG DISABILITAS DI BERBAGAI NEGARA - Widjaja, Gunawan (Penerbit Lafadz Jaya, 2025)
This study compares the political participation of people with disabilities in various countries, highlighting the factors that influence their level of involvement in the political process. Although the political rights of people with disabilities have been legally recognised, their implementation in many countries still face various obstacles, such as limited accessibility, lack of awareness, discrimination, and lack of environmental support. This study employs a qualitative method with a comparative approach through literature analysis. The findings reveal that countries with strong affirmative policies, close collaboration between the government and disability organizations, and accessible technological innovations tend to have higher levels of political participation among people with disabilities. Conversely, in countries still grappling with structural and cultural barriers, participation among this group remains low. This study recommends the need to strengthen regulations, improve accessibility, and provide inclusive political education to achieve equal and meaningful political participation of people with disabilities worldwide.